BIO-IMPLICATION OF ENVIRONMENTALLY EXPOSED MALTED PRODUCTS (CANNED AND PLASTIC MALTINA) ON BIOCHEMICAL INDICES OF ALBINO-RATS - Ahmed, Mariam Glory; Olajide, Joseph Eniola (Global Journal of Medical and Health Science, 2025)
Environmentally exposed carbonated drinks have no biological value; rather, they have, a long-term damaging effect when accumulated in tissues, as discovered in this work. This research was conducted to investigate the biochemical effect of exposing non-alcoholic drinks to direct sunlight or adverse environmental conditions. The experimental set up was made up of malting products consisting of the exposed (Canned and plastic) sample to sunlight for a period of 15 days alongside the unexposed sample as a control. Proximate analysis was performed on the malting samples. The effect of environmental exposure on the product was investigated in an animal model experiment. Twenty-four (24) male rats of wistar strain weighing 120-140g divided into four (4) groups of six rats each, Assessment of liver marker enzymatic; alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkali phosphatase (ALP); and non-enzymatic (albumin and bilirubin) parameters were investigated. The proximate analysis and vitamin, and mineral evaluation showed a decrease in the protein, vitamins and calcium content upon exposure. Assessment of liver function in rat’s serum of the experimental groups showed a significant increase (p < 0.05) in ALP, AST, ALT, and bilirubin and decrease in albumin levels compared with the control unexposed malting sample groups. The findings showed that environmentally exposed malting elicits adverse biochemical and physical changes and therefore portends greater long-term toxicological effects with deleterious action